The 1, 24, 25(OH)3D3 metabolite in clinical and experimental CKD: Impact of calcitriol treatment. Issue 226 (February 2023) - Turner, Mandy E.; Rowsell, Tyler S.; Kaufmann, Martin; Norman, Patrick A.; Neville, Kathryn; Sarabia, Sam; White, Christine A.; Petkovich, Martin; Jones, Glenville; Adams, Michael A.; Holden, Rachel M.
Abstract: Calcitriol, and other vitamin D receptor activators, remain a primary treatment for elevated parathyroid hormone levels in patients with end stage kidney disease. The objective of this study was to assess the 24-hydroxylation-mediated metabolism of 25(OH)D3 and 1, 25(OH)2 D3 in rats with experimental kidney disease treated with calcitriol and in a cross-sectional analysis of patients requiring hemodialysis. Methods: Animals were stratified by creatinine into a time control group or calcitriol (20 ng/kg/day) for 3 weeks following CKD induction using a dietary adenine model (0.25% adenine). Hemodialysis patients were recruited and demographic data including calcitriol prescription was obtained by chart review and participant interview. Vitamin D metabolites were assessed using LC-MS/MS. In the rat model, 1, 25(OH)2 D3 levels increased substantially in calcitriol-treated rats yet there was no increase in its primary metabolite: 1, 24, 25(OH)2 D3 . A lower ratio of 1, 24, 25(OH)2 D3 :1, 25(OH)2 D3 (1, 25-VMR) was associated with increased calcium levels in calcitriol treated rats. In hemodialysis patients (N = 86), the level of 1, 25(OH)2 D3 was substantially higher in calcitriol-treated patients yet there was no difference between groups in 1, 24, 25(OH)3 D3, resulting in a marked decrease in the 1, 25-VMR in calcitriol treated patients. In hemodialysis patients treated with calcitriol, 1, 25(OH)2 D3 and a lower ratio between 1, 24, 25(OH)3 D3 and 1, 25(OH)2 D3 were associated with higher serum calcium levels. Impaired metabolism of exogenous calcitriol may contribute to the adverse effects associated with this treatment. A better understanding of the uniquely dysfunctional catabolic vitamin D profile in CKD may guide more effective treatment strategies. Highlights: Calcitriol is administered therapeutically in chronic kidney disease patients. Exogenous calcitriol 24-hydroxylation does not change in tandem with that of 25(OH)D3 . Reduced catabolic ratios of active compounds correlate with hypercalcemia. Impaired metabolism of calcitriol may contribute to treatment-associated adverse effects. Understanding uniquely dysfunctional catabolism may guide more effective treatment.